نموزج تولية المرأة منصب الأفتاء واختصاتها في ماليزيا - Nur Fatin Binti Halil
This thesis aims to develop a jurisdiction model for female mufti in Malaysia. With the purpose of developing the model, the Islamic and Malaysian laws viewpoints on the appointment of mufti among women is first researched into by the researcher. This study was in the form of qualitative study, utilizing texts and documents analysis to explain the views of the classical and contemporary scholars on the issues of the appointment of female mufti. Moreover, the researcher conducted a focus group interviews to verify the findings of the texts and documents analysis. Results show that, in Islamic law there were no restrictions for women to issue fatwas. However, there were differences of opinion for woman to be appointed as an official mufti. Whilst from the Malaysian law perspective, there shouldn’t be of any hindrances for women becoming a mufti if consent were obtained from either the Sultan, the Head of the State or the Yang di-Pertuan Agong. Nevertheless, mufti’s responsibilities in Malaysia were not only to issue fatwas but involved also in many other commitments and responsibilities. Hence if women be appointed as mufti, some foreseen obstacles in fulfilling some of the commitments especially in the Royal affairs and also in the official and religious activities need to be attend to. Thus, a model of jurisdictions for female mufti in Malaysia with some modification of the existing mufti’s jurisdictions was developed. This model was validated and approved by panel of experts and would become a useful guide for woman be appointed as mufti in the future. Undeniable, the appointment of female mufti would provide huge benefits, consequently empowering women’s participation and especially as policy makers in Malaysia.